Prevalence and associated factors of chronic kidney disease among diabetes mellitus patients in Ethiopia: A systematic review and meta-analysis. - Habtamu Wagnew Abuhay; Melaku Kindie Yenit; Mihret Melese; Gebrie Getu Alemu; Fantu Mamo Aragaw (PLoS ONE)
Introduction Chronic kidney disease (CKD) is a major public health concern worldwide, especially among people with diabetes mellitus (DM), which is the main cause of morbidity and mortality. In Ethiopia, the burden of CKD on DM patients is compounded by a variety of socioeconomic and healthcare-related issues. Despite the increased risk of developing CKD in DM patients, comprehensive studies on the prevalence and associated factors of CKD in this population are rare. To address this gap, this study aimed to estimate the pooled prevalence and associated factors of CKD among DM patients in Ethiopia. Methods This systematic review and meta-analysis was carried out through an investigation of published studies in Ethiopia. A systematic literature search was performed using electronic databases such as PubMed, EMBASE, Scopus, and Google Scholar. A random-effects model was used to estimate the pooled prevalence of CKD and the odds ratio (OR) with a 95% confidence interval. The I² statistic was used to measure heterogeneity among the included studies, with a p-value < 0.05 indicating statistical significance. Publication bias was evaluated via a funnel plot and Egger's test, and subgroup, sensitivity, and meta-regression analyses were also performed. Results Out of the 19 included studies, the estimated pooled prevalence of CKD among DM patients in Ethiopia was 18% (95% CI 14.0, 22.0). In addition, age ≥ 60 years (OR = 3.07, 95% CI: 2.44, 3.87), rural residence (OR = 1.40, 95% CI: 1.01, 1.95), duration of DM > 5 years (OR = 2.47, 95% CI: 1.62, 3.77), proteinuria (OR = 3.30, 95% CI: 2.23, 4.88), HDL-C level < 40 mg/dL (OR = 3.08, 95% CI: 2.28, 4.16), and family history of CKD (OR = 2.58, 95% CI: 1.62, 4.09) were factors significantly associated with the prevalence of CKD among DM patients. Conclusion The prevalence of CKD in Ethiopia was high, affecting nearly two in five individuals with diabetes. In addition, factors such as older age, rural residence, longer DM duration, positive proteinuria, lower HDL-C levels, and a family history of CKD were significantly associated with CKD prevalence. Therefore, targeted public health interventions, such as screening, education, and awareness programs, are highly recommended to mitigate this problem. Systematic review registrations PROSPERO (2024: CRD42024576958).